2008
DOI: 10.1007/s10803-007-0521-y
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Processing in Children with and without Autism Spectrum Disorders

Abstract: Fifteen children with autism spectrum disorders (ASD) and twenty-one children without ASD completed six perceptual tasks designed to characterize the nature of the audiovisual processing difficulties experienced by children with ASD. Children with ASD scored significantly lower than children without ASD on audiovisual tasks involving human faces and voices, but scored similarly to children without ASD on audiovisual tasks involving nonhuman stimuli (bouncing balls). Results suggest that children with ASD may u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
123
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 48 publications
16
123
2
2
Order By: Relevance
“…The McGurk effect (i.e., illusory auditory perception influenced by discordant visual information) has been one frontrunner paradigm for studying MSI in TD individuals as well as in ASD (Foxe and Molholm 2009;Iarocci and McDonald 2006). While some studies have identified a diminished McGurk effect in ASD (Bebko et al 2014;Mongillo et al 2008;Williams et al 2004), others have found that the effect is contingent on developmental factors (Taylor et al 2010), socio-communicative impairments (Iarocci et al 2010, or task-related temporal factors (Woynaroski et al 2013).The speech-in-noise paradigm, which is based on the facilitatory effect of multisensory stimulation, has also been used to better understand multisensory integration processes in typical development as well as in ASD. Using the speech-in noise approach to compare adolescents with Abstract Previous studies have suggested audiovisual multisensory integration (MSI) may be atypical in Autism Spectrum Disorder (ASD).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The McGurk effect (i.e., illusory auditory perception influenced by discordant visual information) has been one frontrunner paradigm for studying MSI in TD individuals as well as in ASD (Foxe and Molholm 2009;Iarocci and McDonald 2006). While some studies have identified a diminished McGurk effect in ASD (Bebko et al 2014;Mongillo et al 2008;Williams et al 2004), others have found that the effect is contingent on developmental factors (Taylor et al 2010), socio-communicative impairments (Iarocci et al 2010, or task-related temporal factors (Woynaroski et al 2013).The speech-in-noise paradigm, which is based on the facilitatory effect of multisensory stimulation, has also been used to better understand multisensory integration processes in typical development as well as in ASD. Using the speech-in noise approach to compare adolescents with Abstract Previous studies have suggested audiovisual multisensory integration (MSI) may be atypical in Autism Spectrum Disorder (ASD).…”
mentioning
confidence: 99%
“…Much of the information on MSI in ASD has originated from studies examining the integration of sensory stimuli that are socio-communicative in nature (i.e., speech and faces; Brandwein et al 2013;Mongillo et al 2008). The McGurk effect (i.e., illusory auditory perception influenced by discordant visual information) has been one frontrunner paradigm for studying MSI in TD individuals as well as in ASD (Foxe and Molholm 2009;Iarocci and McDonald 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Another explanation for the discrepancy in findings may be due to the considerable variation in paradigms used (Marco, Hinkley, Hill and Nagarajan, 2011). Auditory perceptual abilities in ASD may depend on the nature and complexity of the stimulus and the task (Bertone Mottron, Jelenic, and Faubert 2005;Samson et al, 2006;Mongillo et al, 2008).…”
mentioning
confidence: 99%